Complex regional pain syndrome–up-to-date. (November 2017) - Birklein, Frank; Dimova, Violeta
Abstract : Abstract: Complex regional pain syndrome (CRPS) was described for the first time in the 19th century by Silas Weir Mitchell. After the exclusion of other causes, CRPS is characterised by a typical clinical constellation of pain, sensory, autonomic, motor, or trophic symptoms which can no longer be explained by the initial trauma. These symptoms spread distally and are not limited to innervation territories. If CRPS is not improved in the acute phase and becomes chronic, the visible symptoms change throughout because of the changing pathophysiology; the pain, however, remains. The diagnosis is primarily clinical, although in complex cases further technical examination mainly for exclusion of alternative diagnoses is warranted. In the initial phase, the pathophysiology is dominated by a posttraumatic inflammatory reaction by the activation of the innate and adaptive immune system. In particular, without adequate treatment, central nociceptive sensitization, reorganisation, and implicit learning processes develop, whereas the inflammation moderates. The main symptoms then include movement disorders, alternating skin temperature, sensory loss, hyperalgesia, and body perception disturbances. Psychological factors such as posttraumatic stress or pain-related fear may impact the course and the treatability of CRPS. The treatment should be ideally adjusted to the pathophysiology. Pharmacological treatment maybe particularly effective in acute stages and includes steroids, bisphosphonates, and dimethylsulfoxide cream. Common anti-neuropathic pain drugs can be recommended empirically. Intravenous long-term ketamine administration has shown efficacy in randomised controlled trials, but its repeated application is demanding and has side effects. Important components of the treatment include physio- and occupational therapy including behavioural therapy (eg, graded exposure in vivo and graded motor imaging). If psychosocial comorbidities exist, patients should be appropriately treated and supported. Invasive methods should only be used in specialised centres and in carefully evaluated cases. Considering these fundamentals, CRPS often remains a chronic pain disorder but the devastating cases should become rare. Abstract : The pathophysiology of complex regional pain syndromes includes inflammation and central reorganisation. The treatment should be adjusted to the prevailing pathophysiology including possible psychosocial factors.